The Effect of Suggested Physical Exercises to Reduce Wrist Joint Injuries Among Secondyear Gymnastics Students - Ghasaq Taher Habeeb; Ali Barkawi Jleeb; Fawziya Kathem Mohsen; Ali Smoom Fartousy (Journal of Health Sciences and Surveillance System)
Background: Applying trainings and following them during sports training can help reduce the risk of wrist joint injuries and ensure the long-term health and well-being of gymnastics students. The aim of the present study was to evaluate the effectiveness of suggested physical exercises in reducing wrist joint injuries of second-year gymnastics students.Methods: This is a quasi-experimental study with an experimental group and two pre-tests and post-tests was conducted since it is suitable with the nature of the research. Participants consisted of 36 students (age=20±1.5, weight=71.83±3.4, height=175.83±5.5). Special exercises were designed to develop the strength and range of motion to reduce wrist joint injuries. The program included 16 training sessions for a period of 8 weeks (two sessions every week). In general, the special exercises lasted for 2 months; immediately after that, the post-tests were conducted. To evaluate the effect of physical training, we used several instruments and devices. These included a dynamometer to measure the wrist strength, a goniometer to measure the range of the motion of the wrist joint, and a physician digital scale to measure the height and weight.Results: The results showed a significant improvement in the hand wrist strength in all post-measurements compared to pretests. The mean scores of upward flexion strength increased from 17.69 to 19.56, downward flexion strength from 9.33 to 10.91, rightward flexion strength from 13.97 to 15.80, and leftward flexion strength from 10.13 to 12.01. In addition, the range of motion tests showed a significant improvement in all dimensional measurements, as the mean scores of flexibilities of the wrist joint increased when flexed upward from 74.94 to 78.67, flexed downward from 82.83 to 85.89, flexed to the right from 39.39 to 43.44, and flexed to the left from 29.22 to 32.78.Conclusion: The exercises used have a positive effect on improving muscle strength and developing the range of motion of the wrist joint, which protects the joint against damage or recurrence. Therefore, the development of such physical exercises is suggested for other places and similar sports.